The effect of different planting materials ratios on the growth of foliage plants - Kosinwattana, S.; Anuwong, C.; Chatchana, T.; Boonauan, P.; Teamkao, P. (International Journal of Agricultural Technology, 2021)
Growing foliage plants in the containers using soil-based growing media poroved to be a good alternative for the home garden, especially where land is limited. The results revealed that the plant height, the leaf number, the leaf width, and the leaf length of five types of plants in the growing media mixtures of leaf compost: coconut husk chips: coconut coir: sand ratio 2:1:1:1 were higher than other treatments. Therefore, it could suitable use for planting media to reduce the production cost of foliage plants